Linguosemiotic Mechanisms of Manipulative Potential Formation in Polycoded Nomination in Advertising Discourse - R. I. Zakharov (Научный диалог, 2023)
The article is dedicated to the linguo-semiotic analysis of the functioning of polycode names as a manipulative tool in advertising discourse. The aim of the study is to describe the influence of non-verbal components on the expression of the illocutionary force of the name. The material of the study consists of polycode commercial designations identified through the author’s own internet monitoring and direct observation from 2021 to 2023. An examination of the situational context has been conducted, dominant signs in the structure of nomination have been identified, and the expressed meaning has been established. Word-formation models for creating names have been identified, classified according to the means of expressing illocutionary force. The use of similar models by commercial organizations from different fields of activity allows us to speak about the main trends in naming in advertising discourse. The author puts forward a projective hypothesis of manipulative influence: a stimulus-response situation is applied in advertising communication, and manipulation is realized through the tactic of imposition. It has been established that different situations are implicitly related in the message, for which loosely structured stimuli are used, which influence the formation of the addressee’s attitudes and program their behavior. It is concluded that in polycode commercial nominations, the technique of exploiting linguistic and non-linguistic behavioral stereotypes is used.